Influence of Phenology and Post-Harvest Processing of Vegetal Material on the Allelopathy of Annoni Grass (Eragrostis plana) Extracts - SCHEFFER-BASSO,S.M. (2019)
ABSTRACT: The phenological stage, post-harvest processing and quantity of material can interfere in the allelopathic activity of extracts. The objective of this study is to test the allelopathic effect of aqueous extracts of the leaves of Annoni grass (Eragrostis plana), an invader of natural pastures. Twelve extracts were prepared by combining the phenological stage of the plants when harvesting the leaves (vegetative; flowering), post-harvest processing before extraction (fresh; dry at 40 oC), and the amount of plant material (5, 15, and 25 g 100 mL-1 distilled water). Two bioassays were conducted in a germination chamber, with evaluation of germination and growth of seedlings of lettuce (Lactuca sativa) and white clover (Trifolium repens). The extracts with higher allelopathic activity were further developed with 15 and 25 g of dried leaves and harvested in plants at the vegetative stage. Germination was attributed to being the greatest contribution to the divergence between the extracts. White clover was more sensitive to extracts, for which 50% to 67% of the extracts were effectively allelopathic (≥50% inhibition); in lettuce, between 8% and 58% of the extracts exhibited this potential. The phenological stage was the factor with a greater individual effect on the allelopathic activity on lettuce and white clover seedlings, and on lettuce germination. The post-harvest processing responded by the greater variation on germination and germination speed index of white clover. The sensitivity of the white clover to extracts of Annoni grass suggests a compromise of its establishment in pastures with the presence of the invader.